NUANCED POETIC LANGUAGE IN NGUYEN DU’S THE TALE OF KIEU - Nguyễn Thị Nguyệt Trinh (Tạp chí Khoa học Đại học Đà Lạt)
In terms of content, Vietnamese poetry has unique characteristics in relation to the poetry of other countries in the East Asia cultural sphere: Vietnamese poetry is not inclined to neutral meanings but specific, emotional meanings. This article examines the great poet Nguyen Du who had the ability to use nuanced language to express the beauty of the national language in poetry in his masterpiece, “The Tale of Kieu”. We analyze Nguyen Du's writing through the language of “The Tale of Kieu”, especially reduplication and compound words and their role in the work.